2011
DOI: 10.1038/nature10237
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 adaptation to NK-cell-mediated immune pressure

Abstract: Natural Killer (NK) cells play an important role in the control of viral infections, recognizing virally infected cells through a variety of activating and inhibitory receptors1–3. Epidemiological and functional studies have recently suggested that NK cells can also contribute to the control of HIV-1 infection through recognition of virally infected cells by both activating and inhibitory Killer Immunoglobulin-like receptors (KIRs)4–7. However, it remains unknown whether NK cells can directly mediate antiviral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
315
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 318 publications
(322 citation statements)
references
References 29 publications
7
315
0
Order By: Relevance
“…same authors [19]. This study identified more than 20 positions in the HIV-1 genome at which amino acid polymorphisms were significantly associated with the presence of a specific KIR gene [19]. More recently, the same group confirmed that HIV escape mutations also occur in the context of the specific HLA-C ⁄ 03:04/KIR2DLR3 compound genotype [20] that is now studied by Lunemann et al for HCV.…”
supporting
confidence: 58%
See 1 more Smart Citation
“…same authors [19]. This study identified more than 20 positions in the HIV-1 genome at which amino acid polymorphisms were significantly associated with the presence of a specific KIR gene [19]. More recently, the same group confirmed that HIV escape mutations also occur in the context of the specific HLA-C ⁄ 03:04/KIR2DLR3 compound genotype [20] that is now studied by Lunemann et al for HCV.…”
supporting
confidence: 58%
“…(C) Low concentrations of variant peptide (black) can prevent the formation of KIR microclusters in response to the high-affinity peptide (pink) and stall downstream signaling. same authors [19]. This study identified more than 20 positions in the HIV-1 genome at which amino acid polymorphisms were significantly associated with the presence of a specific KIR gene [19].…”
mentioning
confidence: 67%
“…Through any of these mechanisms, NK cells can exert selection pressure on HIV through KIR 63, 93. Conversely, HIV peptides that complex with HLA allotypes and bind inhibitory KIR with high affinity represent NK cell ‘escape’ variants via inhibition of NK cell function 94, 95…”
Section: Kir Geneticsmentioning
confidence: 99%
“…Interactions between KIR3DL1 and HLA class I alleles carrying the Bw4-80I motif are peptide-specific [62], and some peptide residues are directly involved in the binding of KIR3DL1 to its ligand [63]. Along these lines, compelling evidence of the impact of NK cells on virus control in the context of a particular KIR background comes from the observation that HIV-1 evolves to evade NK-cell-mediated immune pressure by selecting for sequence variants that specifically affect KIR binding to HLA class I ligands [64].…”
Section: Insights Into Immune Responses Conferring Spontaneous Contromentioning
confidence: 99%